The Effect of Snowball Throwing Model on The Student’s Vocabulary Mastery at SMA Swasta Rakyat Pancur Batu - Dwi Sugiarti; Nuerlaili (Education & Learning, 2022)
The objective of the research is to find out the effect of applying snowball throwing on the student’s vocabulary mastery of SMA Swasta Rakyat Pancur Batu at tenth grade academic year 2021/2022. This research was used experimental research. The population were 40 students of two classes. The researcher using class X IPA 1 and X IPA 2 as the sample. Class X IPA 1 as the experimental group and X IPA 2 as the control group. The experimental group was taught and treatment by snowball throwing and control group without snowball throwing model. The instrument used to collect data in this research was test there are pre-test and post-test. The researcher found that there was a significant difference between the students? score in experimental group and control group. It was known by the mean score of the post-test in experimental group was higher than mean score of post-test in control group. The value of the t-observed 9.26 was higher than t-table 1.68 at the level of significant 0.05 with degree of freedom (df)=40. Based on the result of this research, the The researcher found that there are the significant effect of applying snowball throwing on the student’s vocabulary mastery of SMA Swasta Rakyat Pancur Batu at tenth grade.